2019
DOI: 10.1002/ecy.2827
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dry‐season irrigation on leaf physiology and biomass allocation in tropical lianas and trees

Abstract: Lianas are more abundant in seasonal forests than in wetter forests and are thought to perform better than trees when light is abundant and water is limited. We tested the hypothesis that lianas perform better than trees during seasonal drought using a common garden experiment with 12 taxonomically diverse species (six liana and six tree species) in 12 replicated plots. We irrigated six of the plots during the dry season for four years, while the remaining six control plots received only ambient rainfall. In y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 64 publications
(141 reference statements)
3
40
2
2
Order By: Relevance
“…Smith‐Martin et al . () found that lianas appeared to explore more soil volume per stem diameter than did co‐occurring trees, yet the present study did not find that lianas had greater root extensions per stem diameter, shoot biomass, or total biomass. Moreover, the measurements herein did not quantify fine root biomass (typically defined as roots < 2 mm diameter), which may play a role in differentiating trees and lianas, if lianas have more fine root mass.…”
Section: Discussioncontrasting
confidence: 86%
See 4 more Smart Citations
“…Smith‐Martin et al . () found that lianas appeared to explore more soil volume per stem diameter than did co‐occurring trees, yet the present study did not find that lianas had greater root extensions per stem diameter, shoot biomass, or total biomass. Moreover, the measurements herein did not quantify fine root biomass (typically defined as roots < 2 mm diameter), which may play a role in differentiating trees and lianas, if lianas have more fine root mass.…”
Section: Discussioncontrasting
confidence: 86%
“…Whether these patterns hold in other types of tropical forests is not known. The present findings that lianas do not have deeper roots than co‐occurring trees are consistent with harvests of 4‐yr‐old lianas and trees in a common garden in Panama (Smith‐Martin et al ., ). Furthermore, a recent study using indirect methods to assess this question for wet forest in French Guiana showed that lianas do not use deeper sources of water than trees, even during the dry season (De Deurwaerder et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations